Secure resource allocation for green two‐way relay networks with mutually untrusted relay and mobile users. Issue 1 (1st January 2020) - Wang, Fei; Qin, Changchun
Abstract : The authors investigate secure resource allocation for an orthogonal frequency division multiple access two‐way relay network, which has several pairs of mobile users (MUs) and one energy harvesting (EH) relay. In this network, the relay is untrusted and each MU pair may also overhear the other MU pairs' confidential information. In particular, to forward information for each MU, the relay adopts power splitting technique to harvest energy from radio frequency signals emitted by each MU. For this scenario, which has hardly been considered, the joint problem of subcarrier allocation, power control, and power splitting ratio selection is formulated, with the aim to maximise the total secrecy rate of all MUs. A suboptimal algorithm with low complexity and satisfactory performance is proposed to solve the formulated non‐convex problem.